Ultrathin two-dimensional hybrid perovskites toward flexible electronics and optoelectronics. Issue 5 (19th July 2021) - Zhang, Junran; Song, Xuefen; Wang, Lin; Huang, Wei
Abstract : Ultrathin hybrid perovskites combine the advantages of 2D morphology and organic-inorganic components. This perspective article provides an updated summary and new insights for their development in flexible electronics and optoelectronics.